Association of statin use with Parkinson's disease: Dose–response relationship - Jeong, Su‐Min; Jang, Wooyoung; Shin, Dong Wook (Movement disorders, 2019)
Background There have been conflicting results on the association between statin use and Parkinson's disease (PD) incidence. Objectives This study investigated the association between time‐varying status of statin use and incidence of PD while considering the dose–response relationship and total cholesterol level. Methods Using the database of the Korean National Health Insurance Service from 2002 to 2015, we examined 76,043 subjects (≥60 years old) free of PD, dementia, and stroke at baseline. The dose of statin use was classified into the following four 6‐month categories (<180, 180‐365, 365‐540, and ≥540 days) for each 2‐year interval. The incidence of PD was identified by the prescription records for any anti‐PD medication with a diagnosis of PD. Results During 10 years of follow‐up, 1,427 PD cases occurred. Statin “ever use” was significantly associated with a high risk of PD incidence (adjusted hazard ratio = 1.28; 95% confidence interval = 1.12‐1.46) when compared with statin nonuse. In terms of a dose–response relationship, although a duration of statin use <365 days was associated with a higher risk of PD, the duration of statin use ≥365 days was not significantly associated with an increased risk of PD. Conclusions Statin use was associated with an elevated PD risk of PD, but long‐term and adherent statin use was not significantly associated with elevated PD risk. However, there was no evidence of benefit with any statin treatment related to PD risk. Our study suggests that there is a complex relationship among cholesterol level, statin use, and PD risk that warrants further studies. © 2019 International Parkinson and Movement Disorder Society